Micromycetes on bark and wood of Podocarpus parlatorei (Podocarpaceae) from Argentina - Catania, M.V. (2010)
Ten species of Ascomycota on bark or wood of Podocarpus parlatorei are described and illustrated. Nemania confluens var. microspora var. nov. and Togninia minutissima comb. nov. are proposed; Botryosphaeria sarmentorum, Ceratostomella pyrenaica, Cochliobolus kusanoi, Heptameria obesa, Hypoxylon duranii, Ophioceras dolichostomum, Tengiomyces indicus, Togninia minima, Trichosphae-ria pilosa are recorded for the first time from Argentina.